REVIEW OF THE MONOGRAPH BY O.V. KRYSHEVYCH “CRIMINAL LIABILITY FOR FRAUD: DOCTRINE, LEGISLATION, PRACTICE” - Lykhova, Sofiia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
According to official statistical reporting, criminal offenses against property are the main group of criminal offenses registered in Ukraine. One of the most common types of criminal offenses against property is fraud (appropriation of someone else's property or acquisition of the right to property by deception or abuse of trust), criminal liability for the commission of which is provided for in Article 190 of the Criminal Code of Ukraine. The monograph is one of the first studies of the criminal-legal characteristics of fraud as a separate criminal-legal institution, which is provided for by several articles of the current Criminal Code of Ukraine. The reviewer concludes that the monograph by O.V. Kryshevych is a complete and independent work, which is prepared at a high scientific and educational-methodological level, characterized by novelty in the field of criminal-legal sciences, provides basic and consistent justification and is a useful contribution to jurisprudence in general, and the activities of state institutions in particular.